Synthetic fluid inclusions XIX. Experimental determination of the vapor-saturated liquidus of the system H2O–NaCl–FeCl2. (1st January 2015) - Lecumberri-Sanchez, Pilar; Steele-MacInnis, Matthew; Bodnar, Robert J.
Abstract: Magmatic-hydrothermal fluids associated with felsic to intermediate composition magmas are generally dominated by (Na ± K)Cl, but often the fluids also contain significant concentrations of FeCl2 . Previously, fluid inclusions containing such fluids were interpreted using the properties of H2 O–NaCl because the effect of FeCl2 on the phase equilibrium and volumetric ( PVTx ) properties of aqueous fluids was essentially unknown. In this study, synthetic fluid inclusion experiments have been conducted to determine the vapor-saturated liquidus phase relations of the system H2 O–NaCl–FeCl2 . Microthermometric and microanalytical measurements on synthetic fluid inclusions have been combined with the limited existing data, as well as with predictions based on Pitzer's formalism, to determine the ternary cotectic and peritectic phase boundaries and liquidus fields. The liquidus is qualitatively similar to those of other ternary systems of H2 O–NaCl plus divalent-cation chlorides (MgCl2 and CaCl2 ) and has been characterized through empirical equations that represent the liquid salinity on the ice- and halite-liquidus surfaces. The ice and halite liquidi intersect at a metastable cotectic curve, which can be used to determine fluid compositions in this system if metastable behavior is observed. Furthermore, based on the experimentally determined liquidus, bulk salinities of natural fluid inclusions can be determined from the last dissolution temperatures of ice and/or halite using the new empirical equations.